Trunk Fat Negatively Influences Skeletal and Testicular Functions in Obese Men: Clinical Implications for the Aging Male - Silvia Migliaccio; Davide Francomano; Roberto Bruzziches; Emanuela A. Greco; Rachele Fornari; Lorenzo M. Donini; Andrea Lenzi; Antonio Aversa (International Journal of Endocrinology)
Osteocalcin (OSCA) seems to act as a negative regulator of energy metabolism and insulin sensitivity. Evidence from male rodents suggests that OSCA may also regulate testosterone (T) synthesis. Using a cross-sectional design, we evaluated OSCA, 25(OH) vitamin D, T, 17β-estradiol (E2), homeostasis model assessment of insulin resistance (HOMA-IR), and body composition in 86 obese (mean BMI = 34) male subjects (18–69 yr old). Independently from BMI, an inverse relationship between trunk fat percentage and plasma T (r2=−0.26, P<0.01) and between HOMA-IR and OSCA levels (r2=−0.22, P<0.005) was found. OSCA levels, as well as vitamin D, decreased significantly for higher BMI with significant differences above 35 (P<0.01). A direct correlation between T and bone mineral density at lumbar (BMDL) and neck (BMDH) (P<0.001, r2=−0.20; P<0.001, r2=−0.24) was found, independently from age. An inverse correlation between E2 levels, BMDL, and BMDH (P<0.001, r2=−0.20; P<0.001, r2=−0.19) was observed. These data provide new evidences that a relationship between trunk fat mass, insulin sensitivity, OSCA and T synthesis occurs. This new relationship with skeletal health has relevant implications for the aging male, suggesting OSCA as a novel marker of metabolic and gonadal health status.